16(X+7)=8(X+1)+2X

Simple and best practice solution for 16(X+7)=8(X+1)+2X equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 16(X+7)=8(X+1)+2X equation:


Simplifying
16(X + 7) = 8(X + 1) + 2X

Reorder the terms:
16(7 + X) = 8(X + 1) + 2X
(7 * 16 + X * 16) = 8(X + 1) + 2X
(112 + 16X) = 8(X + 1) + 2X

Reorder the terms:
112 + 16X = 8(1 + X) + 2X
112 + 16X = (1 * 8 + X * 8) + 2X
112 + 16X = (8 + 8X) + 2X

Combine like terms: 8X + 2X = 10X
112 + 16X = 8 + 10X

Solving
112 + 16X = 8 + 10X

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-10X' to each side of the equation.
112 + 16X + -10X = 8 + 10X + -10X

Combine like terms: 16X + -10X = 6X
112 + 6X = 8 + 10X + -10X

Combine like terms: 10X + -10X = 0
112 + 6X = 8 + 0
112 + 6X = 8

Add '-112' to each side of the equation.
112 + -112 + 6X = 8 + -112

Combine like terms: 112 + -112 = 0
0 + 6X = 8 + -112
6X = 8 + -112

Combine like terms: 8 + -112 = -104
6X = -104

Divide each side by '6'.
X = -17.33333333

Simplifying
X = -17.33333333

See similar equations:

| 2r^2+9r+9= | | (2x^2-18x+16)(x-8)=0 | | x^2+2x-4=56 | | (2x+1)(x+1)=91 | | 4x+x=60 | | 8k-[k+(-4+6k)]= | | x^2+4x=56 | | 0.1n=2 | | 0.90x+.05(8-x)=.10(38) | | 2x^2+2y^2-16x+8y-10=0 | | .35x+.05(8-x)=.10(-32) | | 4w^2-48w+80=0 | | 9x^2+16= | | x=-9x-72 | | x=-9-72 | | 16(X+7)=8(X+1) | | 16X+112=8X+8 | | 4-y^2=0 | | 2x-4(x+1)=(6x+4)+x | | 18x^3-10x^2+63x-35=0 | | 14x+4=11x+1 | | 5y+30=0 | | 11-4[3(a+5)-2a]= | | 14=(.31944)*6.28x | | 66-2x=3x+11 | | -22-3x=10-6x | | 13w^2-81=0 | | 16(2x-3)=4(8x+7) | | 0.55x+.05(14-x)=.10(67) | | -2.6x-5.2=1.2-3x | | 100t^2-9=0 | | p(5)=x^3-x |

Equations solver categories